Is pair programing in Higher Education a good strategy? - Sobral, Sónia Rolland (2020)
Pair programming is by definition two-person programming on the same computer. The technique has been used in many higher education institutions and has been reported in some scientific articles, usually for introductory to programming courses. The aim of this article is to make a situation report analyzing the scientific production on pair programming for curricular units of introduction to programming in higher education, measuring the advantages and disadvantages of the strategy. The sample was composed by 153 articles indexed in Elsevier’s Scopus. The results obtained by bibliometric analysis showed the publication rates, authors, in which journals they are published, which are the organizations and countries that publish the most, which are the most cited articles and what their purpose. The benefits reported are generally better code, improved programming and group skills, advantages for women and reducing the work of instructors. The problems are group compatibility: there are studies that randomly distribute pairs, while other use personality tests or knowledge self-assessment.